Influences on the Educational Environment in the Manufacturing Career in Ecuador - Sópalo , Verónica A. (2022)
In the Academy, Government and Company model, it seeks to take advantage of university dynamics as a knowledge manager and its results are for the creation of business innovation as a leverage for the socio-economic development of society. The study was carried out in the context where the university requires a permanent review of the needs of its environment, the creation of solid academic and social networks and the creation of intermediate associations in textile manufacturing. So, the most appropriate path is based on the interaction of the academic, business, and social triad entities for the innovation of regional productivity in the area of manufacturing and improvement of people's lives.